2017
DOI: 10.1111/jfs.12372
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nonthermal effects of electricity on inactivation kinetics of Staphylococcus aureus and Escherichia coli during ohmic heating of infant formula

Abstract: This study investigated the nonthermal effects of electricity on microbial inactivation kinetics of Staphylococcus aureus and Escherichia coli during ohmic heating (OH) of infant formula. For this, temperature profiles during OH and conventional heating (CV) processes were matched, and the kinetic parameters were compared at temperatures ranging from 57.5 to 65.0 8C. The inactivation kinetics were analyzed using an inactivation model, which allowed the definition of the thermal tolerance from k max and D value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Himoto et al (2008) found lower D values for OH at all analysed temperatures for the total viable aerobes (D values varied from 0.44 to 11.25 min in CH and from 0.38 to 8.64 min in OH) and for Streptococcus thermophilus inactivation (variation from 0.2 to 7.54 min in CH and 0.16-6.59 min in OH). Rodrigues et al (2018) found higher inactivation rates for Staphylococcus aureus for all temperatures investigated: the D values varied from 3.41 to 15.06 min at 57.5°C and from 0.53 to 1.42 min at 65°C in OH and CH, respectively. In the case of E. coli, significantly different values were found only for the lowest temperature analysed.…”
Section: Aspects Concerning Vegetative Speciesmentioning
confidence: 81%
See 3 more Smart Citations
“…Himoto et al (2008) found lower D values for OH at all analysed temperatures for the total viable aerobes (D values varied from 0.44 to 11.25 min in CH and from 0.38 to 8.64 min in OH) and for Streptococcus thermophilus inactivation (variation from 0.2 to 7.54 min in CH and 0.16-6.59 min in OH). Rodrigues et al (2018) found higher inactivation rates for Staphylococcus aureus for all temperatures investigated: the D values varied from 3.41 to 15.06 min at 57.5°C and from 0.53 to 1.42 min at 65°C in OH and CH, respectively. In the case of E. coli, significantly different values were found only for the lowest temperature analysed.…”
Section: Aspects Concerning Vegetative Speciesmentioning
confidence: 81%
“…It is important to emphasize that these two works did not statistically analyse the z value. On the other hand, Rodrigues et al (2018) obtained considerably different values for both microorganisms used: the z values were 9.49°C and 7.91°C for Staphylococcus aureus and 10.13°C and 4.88°C for Escherichia coli using ohmic and conventional heating, respectively. In addition, Pereira et al (2007) also found different values for this parameter studying Escherichia coli cells in goat milk (23.1 and 8.4°C for CH and OH, respectively).…”
Section: Aspects Concerning Spores and Vegetative Cellsmentioning
confidence: 91%
See 2 more Smart Citations
“…Kim et al, 2017;S.S. Kim et al, 2017;Rodrigues et al, 2018;Schottroff et al, 2019;Tian et al, 2018). The high potential of OH for microbial death is related to two aspects: (i) compared to CH, in general the heating ramp is faster and the temperature profile is more homogeneous, reducing processing time, energy costs and losses of desirable compounds; (ii) the presence of nonthermal effects may provide additional inactivation rates.…”
Section: Introductionmentioning
confidence: 99%